A Study on Augmented 3D Display Optimization Based on Holographic Optical Element for High Depth and Magnified Image - Ha, Sungjae; Hwang, Leehwan; Lee, Jaehyun; Gentet, Philippe; Kwon, Soonchul; Lee, Seunghyun (Frontiers in Physics, 2021)
Modern Pepper’s ghost—”floating hologram”—systems generally use transparent screens called half mirrors or foils. this system must have the same screen size as the image size in order to display a large-sized image. Further, depth of the image can only be obtained from the distance between the screen and the display panel. These limitations can be overcome using holographic optical elements (HOE). HOE is made by recording the refractive force of the lens with holographic material. In this study, the numerical values of the reconstructed images were theoretically analyzed through optical ray tracing, and the theoretical design of the reconstructed image size and depth plane was numerically measured and experimentally verified.